Agent-based Cloud commerce - Kwang Mong Sim (2009 IEEE International Conference on Industrial Engineering and Engineering Management, 2009)
In a business model for cloud computing, users pay providers for consumption of their computing capabilities. This work proposes an agent-based testbed for bolstering the discovery of cloud resources and SLA negotiation. In the testbed, provider and consumer agents act as intermediaries between providers and consumers. Through a 4-stage resource discovery process (selection, evaluation, filtering, and recommendation), a set of broker agents match consumers' requests to advertisements from providers. Following the matching of requests to resources, consumer and provider agents negotiate for mutually acceptable resource time slots. Empirical results show that broker agents are successful in matching requests to resources, and consumer and provider agents are successful in negotiating for mutually acceptable time slots.